An overview of muslim spiritual parenting - Bensaid, B.; Bensaıd, Benaouda (MDPI, 2021)
Muslim life on the individual, family, and community levels continues to revolve around fundamental spiritual principles, themes, and values with corresponding meanings that impact purpose of life and even lifestyle. Muslim parents pursue ways and means to nurture their children’s spirituality, strengthen their moral resilience, and shape their identity as effective members of society. This theoretical study explores Islamic insights into spiritual parenting, addressing questions around what defines spiritual parenting and constitutes its core tenets, characteristics and approaches, and principles and guidelines used by Muslims to raise spiritual children. This study identifies a rich Islamic conceptualization and theoretical approach to holistic spiritual parenting that engages with modernity and allows room for adaptation, creativity, and intercultural experience. Further empirical research is needed to shed light on the current dynamics of Muslim spiritual parenting, parents’ struggles, accommodations, adaptations, as well as caregiver resistance in practices of spiritual parenting, which would help us better understand the needs and challenges facing Muslim families today and further enrich our understanding of comparative and cross-cultural parenting in multicultural societies. © 2021 by the author. Licensee MDPI, Basel, Switzerland.
Keywords: Islamic education; Islamic spiritual parenting; Muslim children; Spirituality